Barriers to paediatric pain management as viewed by doctors in the region of Thiès, Senegal: first results - Krechting, Floortje; Cissé, Abdoul Magib; Van De Maele, Karolien; van der Werf ten Bosch , Jutte (Belgian Journal of Paediatrics, 2023)
Background: Effective paediatric pain treatment has been proven to be highly beneficial, both in the short and long term, but remains largely unavailable in developing countries. Given that little is known about what doctors in Senegal see as barriers to paediatric pain management, this information can help to improve current practice in Senegal. In light of the diverse background of patients and parents in Belgium, it can also provide valuable insights to Belgian paediatricians. Objective: The aim of this study was to identify and assess barriers to effective pain management in children, as viewed by doctors working in Senegal. Methods: We used an observational, cross-sectional study design with a single questionnaire. Questionnaires were handed out to 65 doctors. The study was conducted in 2018 in the region of Thiès, Senegal. Results: The response rate was 86%. Respondents found pain evaluation to be more difficult in younger children. Only 15% of doctors always have access to opioids and only 22% have access to a protocol for paediatric pain management. A majority (60%) has not received training in paediatric pain management in the past 5 years. Strikingly, 30% think that opioids should be reserved for children with cancer or for palliative care. Conclusion: The main barriers to effective pain management are access barriers to medication, with low access to opioids. Furthermore, the physicians consider access barriers to protocols and training to be an another important factor. Lack of the latter may explain why we see that some misconceptions regarding pain still exist.